Inversion of Lateral Impact Load Migration History and Trajectory Location Method for Deck Structures Based on the Time-Slicing Method - Hongtao Li; Qihu Sheng; Xianqiang Qu; Yaoguo Xie (Shock and Vibration)
The impact load transfer caused by the landing of a carrier aircraft is a complicated problem in engineering, especially for a deck structure with a known area but an unknown location. This is a crucial structural dynamics inverse problem. The traditional dynamics inverse problem is generally to divide and calibrate the known region through Green’s function, locate the region through the minimum norm of the load data obtained from the measurement response inversion, and obtain the time history. However, this method is mostly aimed at single-peak impacts and cannot deal with impact load migration, that is, with multipeak impacts in the time domain. Therefore, based on the time-slice method, this paper presents a method of locating the impact load migration trajectory and time history inversion for deck structures. A mathematical model is constructed independently through the segmentation and identification of the response, combining the Tikhonov regularization method and the generalized cross-validation (GCV) regularization operator to achieve region calibration and time history inversion and then locating the migration trajectory using a load similarity criterion, thus overcoming the limitation that traditional methods cannot achieve multipeak recognition. At the same time, invalid data are avoided through slice screening, and the accuracy of trajectory recognition is greatly improved. The effectiveness and accuracy of the method are verified based on the influence of different slice lengths on the identification results. The influence of different incidence angles on the results is discussed, and the universality of the method is verified.